2021
DOI: 10.1016/j.crmeth.2021.100101
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering spatial representations from spatiotemporal patterns of rodent hippocampal field potentials

Abstract: SUMMARY Spatiotemporal patterns of large-scale spiking and field potentials of the rodent hippocampus encode spatial representations during maze runs, immobility, and sleep. Here, we show that multisite hippocampal field potential amplitude at ultra-high-frequency band (FPA uhf ), a generalized form of multiunit activity, provides not only a fast and reliable reconstruction of the rodent’s position when awake, but also a readout of replay content during sharp-wave ripples. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Based on first-order Taylor series expansion, the following equation can be derived or where . We then used the Horn-Schunck estimation method to estimate the optical flow based on neighboring frames (Horn and Schunck 1981; Cao et al 2021). The optical flow was represented and visualized by a 2D vector field, with arrows indicating the direction, and the size of arrow proportional to the scale.…”
Section: Star Methodsmentioning
confidence: 99%
“…Based on first-order Taylor series expansion, the following equation can be derived or where . We then used the Horn-Schunck estimation method to estimate the optical flow based on neighboring frames (Horn and Schunck 1981; Cao et al 2021). The optical flow was represented and visualized by a 2D vector field, with arrows indicating the direction, and the size of arrow proportional to the scale.…”
Section: Star Methodsmentioning
confidence: 99%
“…Therefore, details about animals, virus injections, surgical procedures, behavioral tests and recording can be found in the respective publications. 27 , 52 , 53 Besides the aforementioned publications, extensive description of all experiments used in this study can be found in the Buzsaki lab database ( https://buzsakilab.com/wp/projects/entry/67125/ , 28 ; ). Hence, all procedures not relevant for this study will only be briefly mentioned here.…”
Section: Methodsmentioning
confidence: 99%
“…S1 and S2). To decode pain onset, we recorded LFPs (21,22), which are known to remain stable in chronic electrophysiological recordings (23)(24)(25). Here, we recorded LFPs simultaneously from the rostral ACC and the hind limb region of S1 (fig.…”
Section: Design Of a Stable Multiregion Neural Interface To Detect An...mentioning
confidence: 99%
“…In contrast, local field potentials (LFPs), which represent the subthreshold synaptic activity from local neuronal populations (21,22), are relatively stable in chronic recordings. Although their signal stability facilitates clinical applications, LFPs have only recently started to be used for population decoding for BMI applications (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%